2018
DOI: 10.1111/ane.13023
|View full text |Cite
|
Sign up to set email alerts
|

Eslicarbazepine acetate as monotherapy in clinical practice: Outcomes from Euro-Esli

Abstract: These clinical practice data support the use of ESL as monotherapy, as well as adjunctive therapy, for focal-onset seizures, complementing evidence from clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 27 publications
2
15
0
Order By: Relevance
“…The incidence of AEs and discontinuation rate because of AEs in the present study are in line with those reported in other studies of clinical practice and lower than the AEs and discontinuation rates observed in the Phase III monotherapy trial conducted in patients with newly diagnosed epilepsy (41% and 14%, respectively). Although there is potential for underreporting of AEs in observational studies, clinical trials can be prone to magnify the incidence of EAs probably as a result of a less flexible dose adjustment than that adopted in clinical practice.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The incidence of AEs and discontinuation rate because of AEs in the present study are in line with those reported in other studies of clinical practice and lower than the AEs and discontinuation rates observed in the Phase III monotherapy trial conducted in patients with newly diagnosed epilepsy (41% and 14%, respectively). Although there is potential for underreporting of AEs in observational studies, clinical trials can be prone to magnify the incidence of EAs probably as a result of a less flexible dose adjustment than that adopted in clinical practice.…”
Section: Discussionsupporting
confidence: 92%
“…These results are similar to those of the Phase III monotherapy trial that showed that 54% of patients remained seizure free on the first dose (800 mg/d) and 71% of patients were classified as seizure free at their last evaluated dose . In line with these results, seizure freedom rates of 88.2% at 12 months (ie, seizure free for the last 6 months) and 59% at last visit independently of the time point when it occurred were reported for 88 patients receiving ESL as initial monotherapy that were included in Euro‐Esli, a pooled analysis of 14 European clinical practice studies …”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…20 After 12 months, responder and seizure freedom rates were 94.1% and 88.2%, respectively, in patients treated initially with ESL monotherapy, and 93.2% and 77.4%, respectively, in patients treated at the last visit with ESL monotherapy. 21 The most common AEs were dizziness, somnolence, instability/ataxia, and fatigue. 21 In a further multicenter, prospective, clinical practice study, conducted in 17 hospitals in Spain (N = 117), the responder rate after 12 months of ESL monotherapy was 83.0%.…”
Section: Discussionmentioning
confidence: 99%
“…21 The most common AEs were dizziness, somnolence, instability/ataxia, and fatigue. 21 In a further multicenter, prospective, clinical practice study, conducted in 17 hospitals in Spain (N = 117), the responder rate after 12 months of ESL monotherapy was 83.0%. 22 The results reported in these clinical practice studies are generally comparable with those observed in the current study in terms of effectiveness and safety/tolerability.…”
Section: Discussionmentioning
confidence: 99%